Specimen Labelling Errors Just Don’t Cut It in the Operating Room - Lee, Tracey (Operating Room Nurses Association of Canada Journal, 2016)
Action research and focus groups are used to address an identified issue with specimen collection in the operating room environment in a New Zealand District Health Board.